The amount of sodium dodecylsulphate getting into waste water during hair washing process - Ragelienė, Lina; Jasulaitytė, Giedrė (Journal of Environmental Engineering and Landscape Management, 2010)
The investigations were carried out while washing hair with sodium dodecylsulphate solutions of different concentrations i. e., lower than the critical concentration of micelle formation of 4×10–3, 6×10–3, the critical concentration of micelle formation of 8×10−3 and higher than the critical concentration of micelle formation of 10×10−3 mol/l in solutions at 40 °C or 50 °C. The amount of sodium dodecylsulphate that gets into waste water or adsorbs on the hair surface was determined using flame photometry and direct potentiometry methods. Having estimated the results obtained during the analysis of flame photometry and direct potentiometry it has been determined that the largest amount of sodium dodecylsulphate gets into waste water when its concentration is higher than the critical concentration of micelle formation of 10 × 10–3 mol/l. The results of the investigation of washing artificially tainted and non‐tainted hair have demonstrated that the largest amount of sodium dodecylsulphate gets into the environment after hair washing with 10× 10–3 mol initial concentration in solution of 6×10–3 and 8×10–3 mol/l. The results of pH measurements of washing and hair extract solution are in correlation with variation of amount of sodium dodecylsulphate in washing solutions. The measurements of pH show that sodium dodecylsulphate interacts with hair.Article in Lithuanian.Natrio dodecilsulfato kiekis nutekamuosiuose vandenyse, susidarantis plaukų plovimo metuSantrauka. Tyrimai buvo atlikti plaunant plaukus natrio dodecilsulfatu 40 °C ar 50 °C temperatūroje. Naudota skirtingų koncentracijų, t. y. mažesnės nei kritine micelių susidarymo koncentracija – 4×10–3mol/l, 6×10−3mol/l, kritinės – 8×10–3mol/l ir didesnės nei kritinė – 10×10–3 mol/l koncentracijos tirpalai. Natrio dodecilsulfato kiekis, patenkantis į nutekamuosius vandenis arba adsorbuojamas ant plaukų paviršiaus, nustatytas liepsnos fotometrijos ir tiesiogines potencio‐metrijos metodais. Įvertinus gautuosius rezultatus matyti, kad daugiausiai natrio dodecilsulfato patenka į nutekamuosius vandenis, kai jo koncentracija didesnė nei kritine micelių susidarymo koncentracija – 10× 10–3 mol/l, mažiausiai – kai pradinė natrio dodecilsulfato tirpalo koncentracija 4×10–3 mol/l ir 6×10–3 mol/l. Plovimo tirpalų ir plaukų ištraukos pH matavimų duomenys siejasi su natrio dodecilsulfato koncentracijos kitimu plovimo tirpaluose. pH matavimu duomenys rodo, kad natrio dodecilsulfatas sąveikauja su plaukais.Reikšminiai žodžiai: natrio dodecilsulfatas, kritinė micelių susidarymo koncentracija, plaukai, temperatūra, liepsnos fotometrija, tiesioginė potenciometrija.Количество додецилсульфата натрия в сливных водах, образующихся в процессе мытья волосРезюме. Исследования были проведены при мытье волос растворами додецилсульфата натрия разной концентрации, т. е. меньше чем критическая мицеллообразования 4×10–3, 6×10–3 мол/л, критическая мицеллообразования 8× 10–3 мол/л и больше чем критическая мицеллообразования 10×10–3 мол/л при температуре 40 °C или 50 °C. Количество попадаемого в сливные воды или адсорбируемого додецилсульфата натрия было установлено методами пламенной фотометрии и прямой потенциометрии. Оценивая результаты, полученные методами плазменной фотометрии и прямой потенциометрии, видно, что наибольшее количество додецилсульфата натрия попадает в сливные воды, когда его концентрация больше чем критическая мицеллообразования 10×10–3 мол/л. Результаты искусственно загрязненных и незагрязненных мытых волос показали, что наибольшее количество додецилсульфата натрия попадает в окружающую среду, когда мытье проводится раствором 10×10–3 мол/л, а наименьшее количество, когда первичная концентрация раствора равна 4×10–3, 6×10–3 мол/л. Результаты измерения растворов рН и вода после мытья волос коррелируют с количественным изменением додецилсульфата натрия в растворах мойки. Измерение рН свидетельствует о том, что додецилсульфат натрия взаимодействует с волосами.Ключевые слова: додецилсульфат натрия, критическая концентрация мицеллообразования, волосы, температура, пламенная фотометрия, прямая потенциометрия.First Published Online: 14 Oct 2010